Varying Responses of Invertebrates to Biodynamic, Organic and Conventional Viticulture - Bosco, Laura; Siegenthaler, Damaris; Ruzzante, Livio; Jacot, Alain; Arlettaz, Raphaël (Frontiers in Conservation Science, 2022)
Alternative farming methods must be deployed to mitigate the detrimental impacts of intensive agriculture on climate, biodiversity, and ecosystem services. Organic and biodynamic farming are environmental-friendly practices that progressively replace conventional agriculture. While potential biodiversity benefits of organic vs. conventional farming have been studied repeatedly, the effects of biodynamic farming on biodiversity remain ill-understood. We investigated the effects of these three main management regimes, and their interaction with ground vegetation cover, on vineyard invertebrate communities in SW Switzerland. Invertebrates were sampled three times during the vegetation season in 2016, focusing on ground-dwelling (pitfall traps) and epiphytic (sweep-netting) invertebrates, and their abundance was modelled for single, additive, and interactive influences of management and ground vegetation cover. Overall, organic and, but to a lesser degree, biodynamic vineyards provided better conditions for invertebrate abundance than conventional vineyards. On the one hand, there was a significant interaction between management and ground vegetation cover for epiphytic invertebrates with a positive linear increase in abundance in organic, a positive curvilinear relationship in biodynamic but a negative curvilinear response to vegetation cover in conventional vineyards. On the other hand, the abundance of ground-dwelling invertebrates was primarily affected by the management regime alone, i.e. without any interaction with ground vegetation characteristics, leading to much higher abundances in organic compared to conventional vineyards, while biodynamic did not differ from the other two regimes. We interpret the patterns as follows: organic grape production offers more suitable habitat conditions for invertebrates due to a spatially more heterogenous but also less often disturbed (compared to biodynamic management) or destroyed (compared to conventional) ground vegetation cover, in line with the predictions of the intermediate disturbance hypothesis. Biodynamic and conventional viticultural management regimes often provide a habitat that is either too mineral (conventional: ground vegetation widely eliminated) or subject to soil disturbance happening frequently through ploughing (biodynamic). We conclude that alternative farming methods do promote biodiversity in vineyard agro-ecosystems, especially so organic management.